What Do Closed Source Data Tell Us About Lone Actor Terrorist Behavior? A Research Note. Issue 1 (2nd January 2022) - Gill, Paul; Corner, Emily; McKee, Amy; Hitchen, Paul; Betley, Paul
ABSTRACT: This article contributes to the growing body of knowledge on lone-actor terrorism with the incorporation of closed-source data. The analyses presented investigate the antecedent behaviors of U.K.-based lone-actor terrorists leading up to their planning or conducting a terrorist event. The results suggest that prior to their attack or arrest the vast majority of lone-actor terrorists each demonstrated elements concerning (a) their grievance, (b) an escalation in their intent to act, (c) gaining capability—both psychologically and technically and (d) attack planning. The results also disaggregate our understanding of lone-actor terrorists in two ways. First, we compare the behaviors of the jihadist actors to those of the extreme-right. Second, we visualize Borum's (2012) continuums of loneness, direction, and motivation. Collectively the results provide insight into the threat assessment and management of potential lone actors.